Transmission of Methicillin‐Resistant Staphylococcus aureus Infection Through Solid Organ Transplantation: Confirmation Via Whole Genome Sequencing. Issue 11 (22nd September 2014) - Wendt, J. M.; Kaul, D.; Limbago, B. M.; Ramesh, M.; Cohle, S.; Denison, A. M.; Driebe, E. M.; Rasheed, J. K.; Zaki, S. R.; Blau, D. M.; Paddock, C. D.; McDougal, L. K.; et al.
<x xml:space="preserve">Abstract</x> We describe two cases of donor‐derived methicillin‐resistant Staphylococcus aureus (MRSA) bacteremia that developed after transplantation of organs from a common donor who died from acute MRSA endocarditis. Both recipients developed recurrent MRSA infection despite appropriate antibiotic therapy, and required prolonged hospitalization and hospital readmission. Comparison of S. aureus whole genome sequence of DNA extracted from fixed donor tissue and recipients' isolates confirmed donor‐derived transmission. Current guidelines emphasize the risk posed by donors with bacteremia from multidrug‐resistant organisms. This investigation suggests that, particularly in the setting of donor endocarditis, even a standard course of prophylactic antibiotics may not be sufficient to prevent donor‐derived infection.